Stem cuttings and substrates in Dovyalis asexual propagation - Rinaldi, André Renato; Villa, Fabíola; Silva, Daniel Fernandes da; Yassue, Rafael Massahiro (Comunicata Scientiae, 2018)
The objective of this study was to evaluate the asexual propagation of Dovyalis, through the use of substrates and cuttings. Three experiments were conducted in Marechal Cândido Rondon, Paraná State, Brazil, and the first experiment consisted of three removal positions of the cuttings (apical, middle and basal) x 4 Indole butyric acid (IBA) concentrations (0 mg L-1, 1000 mg L-1, 2000 mg L-1 and 3000 mg L-1); the second experiment evaluated the number of leaves in the cuttings (2, 4 and 6) x 3 cutting sizes (10, 15 and 20 cm); and the third experiment evaluated four substrates for rooting. The experiment was carried out in a randomized blocks design, with the first in a 3x4 and the second in a 3x3 factorial, respectively, containing 4 repetitions of 15 cuttings. The third experiment consisted of 5 repetitions of 15 cuttings. After the IBA treatment, the cuttings were taken to rooting in sandy beds during 70 days. The agronomical variables were evaluated. Basal and middle cuttings resulted in root systems with better development. The use of 1666 mg L-1 of IBA favors the Dovyalis cuttings rooting. Cuttings with 15 and 20 cm with four leaves favors the Dovyalis vegetative propagation. Dovyalis cuttings develop better on substrates containing latosol and vermiculite.